1967
DOI: 10.1063/1.1709459
|View full text |Cite
|
Sign up to set email alerts
|

A Family of New Cobalt-Base Permanent Magnet Materials

Abstract: A feasible approach for preparing remanence enhanced NdFeB based permanent magnetic compositesThe magnetocrystalline anisotropy of several intermetallic phases of the type RC06 (R= Y, Ce, Pr, Sm, Yorich and Ce-rich mischmetals) has been investigated, and it is concluded that these alloys are promising candidates for fine-particle permanent magnets. They have extremely high uniaxial anisotropy (K = 5.4 to 7.7 X 10 7 erg/cm 3 ), single easy axis, high saturation (B, = 8500 to 11 200 G) and Curie point (l c =464°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
111
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(123 citation statements)
references
References 5 publications
1
111
0
2
Order By: Relevance
“…Magnetic measurements on powders of several RCo 5 and R 2 (Co,Fe)i 7 compounds 6 " 8 (R = rare earth) soon showed that several of these compounds with light rare earths had promising values of magnetization, Curie temperature, and anisotropy. So far, so good.…”
Section: Rare-earth-cobalt Magnetsmentioning
confidence: 99%
“…Magnetic measurements on powders of several RCo 5 and R 2 (Co,Fe)i 7 compounds 6 " 8 (R = rare earth) soon showed that several of these compounds with light rare earths had promising values of magnetization, Curie temperature, and anisotropy. So far, so good.…”
Section: Rare-earth-cobalt Magnetsmentioning
confidence: 99%
“…Furthermore, these compounds are known to exhibit large magnetocrystalline anisotropy energies up to several meV/f.u. [1]. Thus, compounds of the light REs, such as Y, Ce, Pr, and Sm, with ferromagnetic coupling to the Co sublattice and an easy c axis, are ideal for permanent magnet applications since they combine the aforementioned properties with a high magnetic energy density and high coercivity [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…(BH) max strongly depends on the saturation magnetic polarization (J s = 4πM s or μ 0 M s , where M s is the saturation magnetization) and coercivity (H c ), which originates from the magnetic anisotropy (K 1 ) and ferromagnetic ordering in these materials [5,6]. The rare-earth-based magnets, especially SmCo 5 (K 1 = 17 MJ m −3 and J s = 10.7 kG or 1.07 T) and Nd 2 Fe 14 B (K 1 = 5 MJ m −3 and J s = 16.1 kG) are stronger magnets so far, owing to their high K 1 and J s at room temperature [7,8] and thus have an ever-increasing demand, but further improvement in their performance has been slowing in recent years [2][3][4]. L1 0 -ordered (face-centered tetragonal) FePt alloys have shown superior permanentmagnet properties with K 1 = 7 MJ m −3 and J s = 13.8 kG among the rare-earth-free alloys, but the high cost of Pt is a limiting factor.…”
Section: Introduction and Scopementioning
confidence: 99%